Surveillance and monitoring the cereal rust diseases in Lebanon, Morocco and Tunisia in 2023 - Nazari, Kumarse; El Amil, Rola; Al-Jaboobi, Muamar; Maafa, Ilyass; Kemal, Seid Ahmed; Ramdani, Abdelhamid; Ibriz, Hafid; SBAI, Ibtihel; Ramdhane, Nasraoui; Abdsattar, Bouslimi (International Center for Agricultural Research in the Dry Areas, 2023)
The key components for achieving long-lasting resistance to wheat rust disease and effectively managing the wheat rust disease relies on constantly tracking the movement of the pathogens and studying their pathogenic variabilities. Despite the severe drought conditions in wheat-growing regions of CWANA in 2023, the Regional Cereal Rust Research Center-Turkey in collaboration with national rust surveillance teams conducted rust surveillance in Lebanon, Morocco, and Tunisia, following to the BGRI rust surveillance procedures. The national rust surveillance teams at the Lebanese Agricultural Research Institute, Institut National de la Recherche Agronomique (Morocco), and INSTITUT NATIONAL DES GRANDES CULTURES-TUNISIA (Tunisia) conducted the rust surveys in wheat growing areas. The GPS coordinates of survey sites, the status of rust diseases, and crop phenology were collected and shared with the online Global Cereal Rust Surveillance and Monitoring System following the BGRI standard rust surveillance protocol.